2021
DOI: 10.3389/fchem.2021.689521
|View full text |Cite
|
Sign up to set email alerts
|

O-Glycosylation Landscapes of SARS-CoV-2 Spike Proteins

Abstract: The densely glycosylated spike (S) proteins that are highly exposed on the surface of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) facilitate viral attachment, entry, and membrane fusion. We have previously reported all the 22 N-glycosites and site-specific N-glycans in the S protein protomer. Herein, we report the O-glycosylation landscapes of SARS-CoV-2 S proteins, which were characterized through high-resolution mass spectrometry. Following digestion with trypsin and trypsin/Glu-C, and de-N-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…This modification was enriched in the S1 and S2 subunit, responsible for receptor binding and membrane fusion, respectively [78]. It was also demonstrated that S protein is an O-glycoprotein, displaying a variety composition of O-glycosites and O-glycan in a host cell type-dependent manner [79]. Additionally, the size of O-glycan in the glycosylated S protein appears as a factor that modulates the affinity of virus-receptor interaction.…”
Section: Antigenic Changes In Sars-cov-2mentioning
confidence: 96%
“…This modification was enriched in the S1 and S2 subunit, responsible for receptor binding and membrane fusion, respectively [78]. It was also demonstrated that S protein is an O-glycoprotein, displaying a variety composition of O-glycosites and O-glycan in a host cell type-dependent manner [79]. Additionally, the size of O-glycan in the glycosylated S protein appears as a factor that modulates the affinity of virus-receptor interaction.…”
Section: Antigenic Changes In Sars-cov-2mentioning
confidence: 96%
“…Numerous viruses have demonstrated the relevance of the N-associated glycosylation of envelope proteins for immunological escape, including hepatitis C virus [ 16 , 17 ], HIV-1 [ 18 , 19 , 20 ], hepatitis B virus [ 21 ], herpes simplex virus [ 22 ], and coronaviruses [ 23 , 24 , 25 , 26 ]. In addition to playing a crucial role in epitope camouflage, which represents an efficient method of immune evasion [ 24 , 27 , 28 ], the glycan barrier also enhances viral bonding, entrance, and membrane fusion [ 29 ].…”
Section: Strategies Of Immune Evasion By Sars-cov-2mentioning
confidence: 99%
“…Besides N-associated glycans, low levels of O-glycans in SARS-CoV-2 spike protein have recently been discovered [ 24 , 27 , 28 , 29 ]. While the oligomannose glycan content of SARS-CoV-2 (28%) is greater compared to normal host glycans [ 24 ], it is much lower when compared with the HIV-1 Env, which has 60% oligomannose-type glycans [ 20 , 30 ].…”
Section: Strategies Of Immune Evasion By Sars-cov-2mentioning
confidence: 99%
“…Zhang et al reported the mucin-type O-glycosylation landscapes of SARS-CoV-2 S proteins [ 11 ]. The heavily glycosylated S proteins exposed on the SARS-CoV-2 surface support the attachment, entry and fusion of the virus with host cell membranes.…”
mentioning
confidence: 99%
“…Site-specific O-glycosylation profiling of SARS-CoV-2 S proteins identified 43 non-sialylated O-glycosites in the insect cell-expressed S protein and 30 sialylated O-glycosites in the human S protein. The investigations revealed that the clustered mucin-type O-glycans modified the SARS-CoV-2 S protein, where the O-glycan and O-glycosite composition varied with the host cell type [ 11 ]. He et al reported mucin-induced bronchoalveolar dysfunction in COVID-19 patients [ 12 ].…”
mentioning
confidence: 99%